The Effect of Folic Acid as Supportive Therapy of Spiramycine on Weight of Foetus to Toxoplasma gondii – Infected Pregnant Mice (Mus musculus) - Alfina Azkiana; Boedi Setiawan; Erma Safitri; Lucia Tri Suwanti; Mufasirin Mufasirin; Djoko Legowo (Journal of Parasite Science (JoPS), 2019)
This research aimed to investigate the effect of folic acid as supportive therapy of spiramycine on weight of foetus to Toxoplasma gondii-infected pregnant mice (Mus musculus). Twenty pregnant female mice were divided into four groups as C -, C +, T1 and T2. C +, T1 and T2 were infected by Toxoplasma gondii. C – and C + administered orally 0.5 ml aquadest, T1 administered orally 130 mg/kg BW spiramycine and 0.052 µg/g BW folic acid and T2 administered orally 0.052 µg/g BW folic acid. Experimental groups received the treatments for 5 days, then animals of each groups were sacrified. Foetuses were dissected out for observation. The weight of fetuses were measured using an analytical balance. The data weight of foetuses was presented descriptively and analyzed by ANOVA test and continued by Tukey HSD. From this study, the weight of foetuses from the pregnant mice of T1 and T2 have difference compared with the controls. The result of this research is folic acid affects the weight of foetuses to Toxoplasma gondii-infected pregnant mice.